Hypothyroidism is associated with all‐cause mortality in a national cohort of chronic haemodialysis patients. Issue 6 (10th June 2018) - Lin, Hsuan‐Jen; Lin, Chung‐Chih; Lin, Hsuan Ming; Chen, Hsuan‐Ju; Lin, Che‐Chen; Chang, Chiz‐Tzung; Chou, Che‐Yi; Huang, Chiu‐Ching
Abstract: Aim: The prevalence of hypothyroidism is high in haemodialysis (HD) patients and hypothyroidism increases all‐cause mortality in HD patients. Comorbidities are common in HD patients and are associated with both mortality and hypothyroidism. The aim of the study is to explore the effect of the interactions of comorbidities and hypothyroidism on all‐cause mortality in HD patients. Method: Patients with hypothyroidism (ICD‐9‐CM 244.0, 244.1, and 244.9) and matched patients without hypothyroidism in the Registry for Catastrophic Illness Patient Database of Taiwan Health Insurance from 2000 to 2010 were analyzed. The association of hypothyroidism and risk of all‐cause mortality was analyzed using Cox proportional hazard regression. Result: Nine hundred and eight HD patients with hypothyroidism and 3632 sex‐, age‐, gender‐ matched HD patients without hypothyroidism were analyzed. Hypothyroidism was associated with increased all‐cause mortality with an adjusted hazard ratio of 1.22 [95% confidence interval (CI): 1.10–1.36, P <  0.001]. TRT may decrease mortality associated with hypothyroidism ( P <  0.001). There was a significant interaction ( P =  0.04) between diabetes and hypothyroidism. There was no significant interaction found in hypothyroidism and the following comorbidities: hyperlipidaemia, hypertension, chronic obstructive pulmonary disease, coronary artery disease, stroke, peripheral arterial disease, asthma, congestive heart failure and cancer. Conclusion: Hypothyroidism is associated with increased all‐cause mortality in chronic HD patients. The interaction of hypothyroidism and diabetes, but not other common comorbidities in HD patients, has an effect on mortality risks. Summary at a Glance: Hypothyroidism is associated with increased all‐cause mortality in chronic HD patients in Taiwan. Thyroxin replacement therapy lowers the risk of mortality in a time‐varying Cox proportional hazard regression analysis.